Impact of Smoking on Long-Term Revascularization Success and Complications in Multivessel Percutaneous Coronary Intervention: A Retrospective Cohort Study - Shah, Tariq; Shah, Syed Muzammil; Khan, Fahad Raja; Rafi Ullah; Muhammad, Abdul Wahab; Syed, Kashif ur Rahman (Indus Journal of Bioscience Research, 2024)
Background: Smoking is a major modifiable risk factor in coronary artery disease (CAD) and is associated with adverse outcomes following percutaneous coronary intervention (PCI). PCI, widely utilized for revascularization in multivessel CAD, aims to restore coronary blood flow and reduce ischemic complications. However, smokers face increased risks of restenosis and major adverse cardiac events (MACE) after PCI, highlighting a need for further investigation into these associations. Objective: This study aimed to assess the impact of smoking on revascularization success and complications in patients undergoing multivessel PCI. Methods: A retrospective cohort study was conducted at a tertiary cardiovascular center, evaluating clinical data from patients who underwent PCI from January 1, 2023, to December 31, 2023. Patients aged 18 and older with confirmed multivessel CAD were included. Participants were divided into smokers (N=779) and non-smokers (N=779) based on documented smoking status. All patients underwent PCI with either drug-eluting stents (DES) or drug-eluting balloons (DEB), followed by standard dual antiplatelet therapy. The primary outcome was revascularization success, defined as achieving TIMI grade ≥2. Secondary outcomes included incidences of MACE and restenosis. Statistical analyses were performed using SPSS v27, with t-tests and chi-square tests used for continuous and categorical variables, respectively. Logistic regression adjusted for confounders. Results: Revascularization success was significantly lower in smokers (69.8%) compared to non-smokers (81.6%) (p < 0.001). Smokers also exhibited higher rates of MACE (15.5%) and restenosis (12.6%) versus 8.4% and 7.3% in non-smokers, respectively (p < 0.001 for both outcomes). Conclusion: Smoking negatively affects revascularization success and increases MACE and restenosis risks in multivessel PCI patients. These findings underscore the importance of tailored therapeutic strategies and smoking cessation efforts to improve PCI outcomes in this high-risk group.